Faktor Yang Berhubungan Dengan Kelelahan Kerja Perawat Ruang Rawat Inap Rsud Andi Djemma Masamba (Window of Public Health Journal, 2025)
The 2023 International Labour Organization (ILO) report stated that more than 70% of healthcare workers in developing countries reported symptoms of work fatigue due to disproportionate workloads and suboptimal HR management systems. This study aims to explain the factors associated with work fatigue in nurses in the inpatient ward of Andi Djemma Masamba Regional Hospital. This type of research is a quantitative cross-sectional study design conducted in May [2025]. The population consisted of 214 nurses at Andi Djemma Masamba Regional Hospital, with a sample of 48 nurses selected using simple random sampling. The sample is part of the study population that is considered representative of the entire population. This number was obtained from calculations using the Lemeshow formula. Data were collected through questionnaires and analyzed univariately and bivariately. The results showed a significant relationship between work shifts (p = 0.002), workload (p = 0.000), and psychosocial factors (p = 0.001) with the level of work fatigue in nurses in the inpatient ward of Andi Djemma Masamba Regional Hospital. It is recommended that hospitals implement strategies such as optimizing shift schedules, reducing workload, and providing psychosocial support to reduce nurse fatigue and improve patient outcomes effectively.